Unclaimed Luggage - Antoniou, Klitsa (My University, 2026)
Unclaimed Luggage, Text: Mercedes Kemp, Cerculo de Bellas Artes, Madrid 2005 Mare Nostrum: Visions of a Mermaid, Diatopos Center of Contemporary Art, Text: Antonis Danos. En Tipis Publications, Cyprus 2004